Relation Between Perception of Control of COVID-19 Pandemic and Cyberchondria Levels in Individuals With Chronic Diseases - Bahçecioğlu Turan, Gülcan; Özer, Zülfünaz; Teke, Neslihan; Teke, Neslihan (My University, 2021)
Objective: Perception that internet is a reliable source for information on COVID-19 could increase the search intensity for more information, consecutively increasing confusion and distress feelings, thereby could contribute to cyberchondira during pandemic. This study was done to investigate the relationship between perception of control of COVID-19 pandemic and cyberchondria levels in individuals with chronic diseases. Material and Methods: This descriptive and correlational study was done between December 1-30, 2020 by snowball sampling method. Data collection forms prepared by GoogleDocs program were sent online (e-mail, whatsapp) to individuals older than 18 who had chronic diseases, and they were asked to fill out and share the forms with other people. In the study, 267 individuals responding to the questionnaire were included. Data were collected by “Introductory Information Form,” “Perception of Control of COVID-19 Scale (PCo-COVID-19)” and “Cyberchondria Severity Scale (CSS-15).” Results: Mean age of the participants was 58.07 ± 18.31, 65.8% were female, 71.8% were married, 41.7% were literate, 27.4% were retired, 63.9% had balanced income and expenses and 28.9% had diabetes. CSS-15 mean score was found as 29.51 ± 7.14, compulsion subscale as 3.99 ± 2.03, distress subscale as 4.59 ± 2.33, excessiveness subscale as 5.46 ± 3.35, reassurance subscale as 5.52 ± 3.12 and mistrust of medical professional subscale mean score was found as 9.944.62. Mean score for PCo-COVID-19 was determined as 3.37 ± 0.70, for macro control subscale as 3.46 ± 0.92, for micro control subscale as 3.47 ± 0.78, and for controllability subscale as 3.17 ± 0.89. A significant and negative relation was found between PCo-COVID-19 and CCS-5 total and distress subscale. There was significant and negative relation between macro control and CCS-15 total and distress, excessiveness and reassurance subscales. Also there was a significant negative relation between micro control and CCS-15 total and distress subscale. Conclusion: Individuals participating in the study were found to have high COVID-19 control perception and low cyberchondria levels. As the perception of control of COVID-19 increases, cyberchondria levels decrease.

Amaç: İnternetin COVID-19 ile ilgili bilgilerin güvenilir bir kaynağı olarak algılanması, daha fazla bilgi için aramaları yoğunlaştıracak ve kafa karışıklığı ve sıkıntı hissini artıracak ve böylece salgın sırasında siberkondriye katkıda bulunacaktır. Araştırma, kronik hastalığı olan bireylerde COVID-19 salgını kontrol algısı ile siberkondri düzeyleri arasındaki ilişkiyi incelemek amacıyla yapılmıştır. Gereç ve Yöntem: Kesitsel tanımlayıcı ve ilişki arayıcı tipte olan araştırma, 1-30 Aralık 2020 tarihleri arasında gerçekleştirildi. Anket formu online olarak 18 yaş ve üstü kronik hastalığı olan bireylere gönderildi. Anketlere geri dönüş sağlayan 267 kişi araştırmaya edildi. Veriler “Tanıtıcı Bilgi Formu,” “COVID-19’un Kontrolü Algısı Ölçeği (PCo-COVID-19)” “Siberkondri Ciddiyeti Ölçeği (SCI-15)” kullanılarak toplanmıştır. Bulgular: Bireylerin SCI-15 puan ortalaması 29,51 ± 7,14, zorlantı alt boyutu 3,99 ± 2,03, aşırı kaygı alt boyutu 4,59 ± 2,33, aşırılık alt boyutu 5,46 ± 3,35, içini rahatlatma alt boyutu 5,52 ± 3,12 ve doktora güvensizlik alt boyutu 9,94 ± 4,62 olarak saptanmıştır. PCo-COVID-19 puan ortalaması 3,37 ± 0,70, makro kontrol alt boyutu 3,46 ± 0,92, mikro kontrol alt boyutu 3,47 ± 0,78 ve kontrol edilebilirlik alt boyutu puan ortalaması 3,17 ± 0,89 olarak saptandı. PCo-COVID-19 ile SCI-15 toplam ve aşırı kaygı alt boyutu arasında negatif yönde anlamlı bir ilişki bulundu. Makro kontrol ile SCI-15 toplam ve alt boyutlarından aşırı kaygı, aşırılık ve içini rahatlatma alt boyutları arasında negatif yönde anlamlı bir ilişki bulundu Mikro kontrol ile SCI-15 toplam ve aşırı kaygı alt boyutu arasında negatif yönde anlamlı bir ilişki saptanmıştır. Sonuç: Bireylerin COVID-19 kontrol algısı yüksek, siberkondri düzeyleri düşük bulunmuştur. Bireylerin COVID-19 kontrol algısı yükseldikçe siberkondri düzeyleri azalmaktadır.
Kronik Hastalığı Olan Bireylerde COVID-19 Salgını Kontrol Algısı İle Siberkondri Düzeyleri Arasındaki İlişki
Keywords: COVID-19; Perception of control; Cyberchondria; Chronic disease; COVID-19; Kontrol algısı; Siberkondri; Kronik hastalık